Detection of avian influenza virus. - Omar, Abdul Rahman; Ideris, Aini; Ong, Wee Theng; Syed Hassan, Sharifah; Zulkifli, Hazalina (2006)

(untitled)
The present invention provides a method of simultaneously detecting influenza virus type A and subtyping of the H9N2 subtype of influenza virus type A that cause respiratory infections in avian species. The method includes providing a nucleic acid prepared from a suspected biological sample, amplifying the nucleic acid with a set of primers specific for target genomic regions of avian influenza virus, and detecting the amplification products. Detection of amplification products specific for all the target genomic regions indicates the presence of H9N2 subtype of avian influenza virus. Also disclosed are nucleic acid sequences of SEQ ID NOs: 1 ? 6, for simultaneous detection of influenza virus type A and subtyping of H9N2 subtype of influenza virus type A. The invention also relates to a diagnostic kit for carrying out the inventive method.